In defence of the Prem'sāgar: re-evaluating the narrative of the Hindi-Urdu split - Liu, Gautam (Language ideologies and the vernacular in colonial and postcolonial South Asia, 2023)
This chapter questions the claim that the prose literature of a once-common language was bifurcated into Hindi and Urdu with the foundation of Fort William College in 1800. It provides literary evidence that Hindi and Urdu had a distinct register from the very beginning. The language munshis of that institution adhered to this tradition notwithstanding the pressure to produce textbooks in a mixed variety the colonial masters called Hindustani. Lalluji Lal‘s Premˡsāgar (1810) is often referred to as the starting point of a deliberate process to cleanse Hindi prose from foreign words with British rule functioning as the catalyst of the Hindi-Urdu split. A closer look at the historical context, genre and language of this first printed book of Khari boli Hindi will reveal a different picture, though. With that in mind, the underlying agenda against the Premˡsāgar that solely depicts it as an outcome of linguistic purism will be critically addressed.